Quality of Life and cost of living in lung cancer patients - Kiranoudi, Aggeliki; Kalogianni, Antonia; Kapadochos, Theodoros; Kouris, Ioannis; Douki, Stamatina; Kyriakopoulos, Antonios; Toylia , Georgia (Health & Research Journal, 2025)
Introduction: Lung cancer accounts for about 34% of cancer deaths in men and 23% in women. Advances in treatment options for lung cancer patients are increasing the survival rate and improving the quality of life. Aim: To explore the quality of life of lung cancer patients in Greece as well as to estimate the change in their cost of living. Methods: This is a prospective descriptive observational study. In total, 170 participants were enrolled in the study. Data collection was performed by using a questionnaire of both open-ended and closed-ended questions. Data analysis was performed using SPSS ver. 21.0 (Statistical Package for Social Sciences). Results: The mean age of patients was 67.4 years, while 72.4% of patients were male. The majority of the patients (71.2%) were retired and 13.6% were employed. The average cost of living due to the disease during the previous semester was €4.518. Patients with lower total cost of living had better general health (p=0,006). Patients who resided with more people, with higher monthly family income and lower total cost of living, had better mental health (0.016, 0.027, 0043, respectively). Conclusion: The main goal of the therapeutic approach is the quality of life of cancer patient alongside the effectiveness of the treatment. Determining the factors affecting quality of life that the patient considers important is crucial, with cost of living consisting as one of them. Strategies for reducing the cost of living for cancer patients should be considered.